Flooding tolerance of transgenic tomato plants expressing the bacterial enzyme ACC deaminase controlled by the 35S, rolD or PRB-1b promoter - Grichko, V.P. (University of Waterloo (Canada). Department of Biology); Glick, B.R (Plant physiology and biochemistry, 2001)
Transgenic tomato plants Lycopersicon esculentum (Solanaceae) cv. Heinz 902 expressing the bacterial gene 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase, under the transcriptional control of either two tandem 35S cauliflower mosaic virus promoters (constitutive expression), the rolD promoter from Agrobacterium rhizogenes (root specific expression) or the pathogenesis related PRB-lb promoter from tobacco, were compared to non-transformed plants in their response to flooding stress. Characteristics that were studied include shoot height, and fresh and dry weight; epinasty; ACC deaminase activity; ethylene production; and leaf chlorophyll and protein content. All of the transgenic tomato plants expressing ACC deaminase showed some increased tolerance to flooding stress and were less subject to the deleterious effects of root hypoxia on plant growth than were non-transformed plants. Plants that included an ACC deaminase gene under the control of the rolD promoter were protected to the greatest extent